The Role of Personality Psychology in Islamic Religious Education - Ahmad Yusuf; Mirza Mahbub Wijaya; Ahmad Mohdlori; Hadi Susilo; Muhamad Ansori; Muchammad Nuryadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article aims to discuss the role of personality psychology in Islamic Education. This research is a literature study with a descriptive-analytic approach. This research background is about the concept and definition of Personality psychology and its roles in Islamic Education. From the discussion of this article, it can be concluded that personality is a characteristic inherent in a person that distinguishes individuals from one another. Meanwhile, personality psychology is a science that specifically studies the symptoms of a person's psychological phenomena related to personality, namely the character, nature, and behavior of humans in daily life. There are many different definitions of personality in psychology. However, as a whole, it shows an understanding that fundamental, namely personality, is about individual differences. Meanwhile, in terms of the contribution of Personality Psychology, it has a crucial role in the educational process. Learning can run well if the teacher/educator can understand the characteristics of students as learning subjects in school institutions. Artikel ini bertujuan membahas peran psikologi kepribadian dalam Pendidikan Agama Islam. Jenis Penelitian ini adalah literatur dengan pendekatan deskriptif analitik. Penelitian ini dilatarbelakangi oleh masalah bagaimana konsep dan definisi psikologi kepribadian serta bagaimanakah peranannya dalam Pendidikan Agama Islam. Hasil penelitian menunjukkan bahwa kepribadian adalah ciri khas yang melekat pada diri seseorang yang membedakan individu satu dengan yang lainnya. Sedangkan psikologi kepribadian adalah ilmu yang secara khusus mempelajari gejala fenomena kejiwaan seseorang yang berkaitan dengan personalitas, yaitu watak, sifat dan tingkah laku manusia dalam kehidupan sehari-hari. Terdapat banyak perbedaan pengertian mengenai kepribadian dalam psikologi. Akan tetapi, secara keseluruhan menunjukkan adanya kesepahaman bahwa yang mendasar yaitu personalitas adalah mengenai perbedaan individual. Sedangkan dalam hal kontribusi, psikologi kepribadian memiliki peranan yang sangat penting dalam proses pendidikan. Pembelajaran dapat berjalan dengan baik apabila dalam pelaksanaannya guru/pendidik memiliki kemampuan memahami karakteristik peserta didik selaku subyek pembelajar dalam lembaga sekolah.